Antithrombin V: Critical Evaluation of its Assessment and Properties - Vermylen, Carl; Verstraete, Marc (Thrombosis and Haemostasis, 1961)
1. The techniques used for assessment and detection of antithrombin V are discussed in detail.2. The differentiation of antithrombin V from other causes, which may prolong the thrombin time, are presented.3. The criteria were determined, which at the present time are required for the recognition of antithrombin V. Complementary experiments to perform in one case with antithrombin V are suggested.4. The differentiation of the antithrombin from an antifibrinogen, as was proposed by Loeliger and Hers, is critically reviewed. A new base to classify the inhibitors of the fibrinogen conversion mechanism is proposed.